Chaudhuri’s Dashboard of Vitals in Parkinson’s syndrome: an unmet need underpinned by real life clinical tests - Qamar, Mubasher A.; Rota, Silvia; Batzu, Lucia; Subramanian, Indu; Falup-Pecurariu, Cristian; Titova, Nataliya; Metta, Vinod; Murasan, Iulia; Odin, Per; Padmakumar, Chandrasekhara; Kukkle, Prashanth L.; Borgohain, Rupam; et al. (Frontiers in Neurology, 2023)
We have recently published the notion of the “vitals” of Parkinson’s, a conglomeration of signs and symptoms, largely nonmotor, that must not be missed and yet often not considered in neurological consultations, with considerable societal and personal detrimental consequences. This “dashboard,” termed the Chaudhuri’s vitals of Parkinson’s, are summarized as 5 key vital symptoms or signs and comprise of (a) motor, (b) nonmotor, (c) visual, gut, and oral health, (d) bone health and falls, and finally (e) comorbidities, comedication, and dopamine agonist side effects, such as impulse control disorders. Additionally, not addressing the vitals also may reflect inadequate management strategies, leading to worsening quality of life and diminished wellness, a new concept for people with Parkinson’s. In this paper, we discuss possible, simple to use, and clinically relevant tests that can be used to monitor the status of these vitals, so that these can be incorporated into clinical practice. We also use the term Parkinson’s syndrome to describe Parkinson’s disease, as the term “disease” is now abandoned in many countries, such as the U.K., reflecting the heterogeneity of Parkinson’s, which is now considered by many as a syndrome.